A systematic review and meta-analysis of breastfeeding and neurodevelopmental outcomes in preterm infant - Zhang, Ruolin; Ying, Erya; Wu, Xiujuan; Qin, Han; Guo, Yanping; Guo, Xin; Yu, Zhangbin; Chen, Jun (Frontiers in Public Health, 2024)
BackgroundPrematurity significantly impacts neonatal health worldwide, necessitating effective interventions to improve outcomes for these vulnerable infants. While breastfeeding has emerged as a cornerstone of preterm care, its precise impact on neurodevelopment remains a subject of ongoing inquiry and debate. This systematic review aims to investigate the existing evidence in this area.MethodsOn December 17, 2023, online databases including PubMed, The Cochrane Library, Embase, Web of Science, CNKI, VIP, CBM, and Wan Fang Data were searched. Comparisons were classified into several categories: never breastfeeding (Never-BF) versus exclusive breastfeeding, Never-BF versus any breastfeeding (Any-BF), predominant preterm formula (Pre-PTF) versus predominant breastfeeding (Pre-BF), and Pre-PTF versus predominant donor breast milk (Pre-DBM) groups. Randomized controlled trials and observational studies were analyzed separately through meta-analyses. Each study’s risk of bias was assessed, and the GRADE system was utilized to evaluate the certainty of the findings.ResultsSixteen studies met the inclusion criteria, comprising one RCT and 15 cohort studies. The key findings indicated that infants in the Any-BF groups demonstrated superior long-term cognitive scores compared to those in the Never-BF groups, particularly evident in infants assessed before 18 months in the Pre-BF groups versus Pre-PTF groups. A reduced risk of neurodevelopmental impairment was also observed in preterm infants in the Any-BF groups. Evidence regarding the effect of breastfeeding on motor development was inconclusive, except for potential motor improvement in extremely low birth weight infants in the Any-BF groups. Neither exclusive breastfeeding nor pre-DBM exhibited clear superiority over Pre-PTF in terms of neurodevelopmental outcomes for preterm infants. Caution is warranted due to potential publication bias impacting the assessment of breastfeeding’s impact on motor skills.ConclusionOur systematic review supports current recommendations for breastfeeding in preterm infants, emphasizing its positive effects on cognitive abilities and reduced risk of neurodevelopmental disorders. Further studies are needed to clarify if DHM provides neurodevelopmental benefits comparable to maternal milk, as current evidence does not sufficiently address this question. Additionally, future investigations should prioritize refining our understanding of the influence of breastfeeding on motor development in this vulnerable population.Systematic review registrationPROSPERO, identifier CRD42023492274, Available at: https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023492274.